Menggali Harta Karun Lokal: Mengubah Tempurung Kelapa menjadi Arang Briket di Desa Malaka, Lombok Utara - I Gusti Ngurah Oka Widjaya (PENTAHELIX: Jurnal Ilmiah Pengabdian Pariwisata, 2023)
The Community Service Activities (PKM) in Malaka village are dedicated to enhancing the local community in multiple ways, including economic development, environmental preservation, reducing reliance on oil and gas fuel, and creating high-value products. These activities consist of socialization through lectures, discussions, and simulations/practices. Through PKM, the Malacca community has gained increased knowledge and awareness about the conversion of Coconut Shells into Briquette Charcoal. Additionally, it strives to foster sustainable tourism, thus making a positive impact on the local economy and environmental conservation efforts. The program aims to equip the people of Malacca with skills to effectively utilize their local resources by transforming Coconut Shells into economically valuable and eco-friendly Briquette Charcoal.